FROM GOTHIC TO NEO-GOTHIC: FRANKENSTEIN NOVEL INTO LISA FRANKENSTEIN (2024) FILM ADAPTATION BY ZELDA WILLIAMS - Putri, Marchelinda Okta Brianti Eka; Pujiati, Hat (Universitas Padjadjaran, 2025)
This study aims to show the transformation of the Gothic genre from Frankenstein’s novel to the Neo-Gothic genre in Lisa Frankenstein’s film and to reveal the underlying motives. This qualitative research uses Linda Hutcheon and O’Flynn’s Adaptation theory and is supported by Nick Lacey’s Image and Representation analysis technique. The data are narrative events from the Frankenstein novel in the form of words, phrases, and paragraphs, as well as narrative events in Lisa Frankenstein’s film in the form of screenshots containing frames per scene, dialogue, sound, backsound music, and film shooting techniques. The collected data is analyzed comparatively between the narration in the novel and the film, by reading images and representation analysis techniques in Lacey’s Barthesian semiotics perspective, and discursively as proposed by Linda Hutcheon in the theory of adaptation. The results of the study show that the Lisa Frankenstein film adaptation turns into a feminine style of the creation through the playfulness of the dark comedy narration of Lisa’s domestic skills in reviving the crature. The dark comedy is in line with romantic and sexual relationships between Lisa and the creature, which shows the transformation of genre from gothic novel into neo-gothic film. The transformations shown in the film are influenced by the director’s agency as an adapter and the involvement of various parties, such as Hollywood, which aims to provide novelty to maintain audience interest and maximize the sales profit.